PERANCANGAN APLIKASI GAME EDUKASI PEMBELAJARAN ANAK USIA DINI MENGGUNAKAN LINEAR CONGRUENT METHOD (LCM) BERBASIS ANDROID - Dora Irsa; Rita Wirya Saputra; Sri Primaini (UNIVERSITAS INDO GLOBAL MANDIRI)
Early childhood learning is an approach to development that is intended for children from birth until the age of eight years is done through the provision of educational stimulus to assist the growth and development of the physical and spiritual so that children have the readiness to enter further education. To assist the growth and development of children then built an educational game. Educational game is a game that apply learning and educational material inserts into the game. Educational game that will be developed is a game (game) to train children early age especially those aged three to eight years to be able to read, write and count properly. This educational game called calistung game. Educational game calistung applied into the android operating system. And for the determination of the matter calistung presentation using a linear congruent method (LCM). Linear congruent method (LCM) is one method of random number generator. Where the determination of the constants LCM (a, c and m) will determine whether or not the random number obtained in the sense of obtaining random numbers as if nothing happened looping.